Improving Post-Secondary Academic and Professional Staff Wellbeing: A Literature Synthesis - Cameron W Smith (Canadian Society for Studies in Education, 2020)
Numerous studies attest to the increasing levels of stress and reduced wellbeing reported by post-secondary academic and professional staff. Despite the growing wealth of research on individual and organizational (workplace) wellbeing, there is a lack of synthesis on the context and effect of interventions supporting the wellbeing of post-secondary staff. To support understanding these knowledge gaps, this literature synthesis provides an overview of studies on organizational and individual wellbeing, focusing on interventions and considerations to support post-secondary staff. As institutions invest in wellness programs and navigate contradictions, this review can support faculties and administrators in higher education when seeking to address staff wellbeing. This review describes a range of practices and considerations for supporting wellbeing and work-life effectiveness, with a focus on studies conducted in post-secondary settings whenever possible.